Progressive sketching with instant previewing - Wang, Kai (2020)
Sketch-based modeling uses freeform strokes as basic modeling metaphor and the modeling process typically involves two phases: sketching and sculpting. This paper presents a method to enhance the sketching phase to have the features of both sketching and sculpting. The key idea of the method is progressive sketching with instant previewing, which has the capacity of intuitively creating complex initial shapes that interpolate all the sketched strokes. The process lets the user iteratively sketch and meanwhile updates the reconstructed 3D shape instantly, which enables the user to be aware of the up-to-date shape. The underlying technique supporting this process is a novel surface construction algorithm that produces 3D triangular mesh models typically with only a single connected component and gradual shape changes during iterative sketching as well. To demonstrate the capability of the method, a sketching-based modeling prototype is also developed, which includes both sketching and sculpting functions. Experiments show that the proposed method can allow users to intuitively and flexibly create and edit 3D models even with complex topology, which is usually difficult for conventional sketch-based modeling systems.